EXPERIENCE OF MOMETASONE APPLICATION FOR THE TREATMENT OF PHOTODERMATOSES AMONG CHILDREN - L.K. Aslamazyan; T.S. Shaipov; E.I. Pil'gui (Педиатрическая фармакология)
The authors described the experience of the topical glucocorticoid mometasone application among children with photoder matoses (solar burns, photocontact dermatitis). They came to conclusion that the medication was highly efficient and well tolerable.Key words: photodermatoses, treatment, mometasone, children.